Insecure Digital Frontiers: navigating the global cybersecurity landscape - Bhardwaj, Akashdeep (Abingdon, Oxon : Routledge / CRC Press, 2025)
An immersive exploration into the vulnerabilities and threat-landscape of global cybersecurity, offering actionable insights for individuals, organizations and policymakers.
Includes index.
Keywords: Computer security; Digital forensics; Cybersecurity